Monochorionic Triplet Gestation after Single Blastocyst Transfer Using Donor Oocytes: Case Report and Review. (28th July 2020) - Ferri, G.; Musto, M.; Colombo, G.; Savasi, V. M.
Abstract : We report a case of a 43-year-old patient with a monochorionic triamniotic triplet pregnancy after IVF with donor oocytes. After failed IVF attempts, the patient chose to undergo treatment with donor oocytes. Her 22-year-old oocyte donor underwent standard controlled ovarian hyperstimulation. The retrieved oocytes were fertilized in vitro, and one embryo was transferred at the blastocyst stage. At 6 weeks and 5 days of gestation, an ultrasound revealed monochorionic triamniotic (MCTA) triplets. The risk of monozygotic twinning in women undergoing in vitro fertilization (IVF) is reported to be higher than that in natural conception, although the causes of the phenomenon have not yet been clarified. Efforts still must be made in order to prevent monozygotic multiple pregnancies, associated with much greater chances of obstetric and perinatal morbidity and mortality.